Size dependence of the propulsion velocity for catalytic Janus-sphere swimmers. - Ebbens, S; Tu, M; Howse, JR; Golestanian, R (2012)
The propulsion velocity of active colloids that asymmetrically catalyze a chemical reaction is probed experimentally as a function of their sizes. It is found that over the experimentally accessible range, the velocity decays as a function of size, with a rate that is compatible with an inverse size dependence. A diffusion-reaction model for the concentrations of the fuel and waste molecules that takes into account a two-step process for the asymmetric catalytic activity on the surface of the colloid is shown to predict a similar behavior for colloids at the large size limit, with a saturation for smaller sizes.